Review of Spontaneous Pneumothorax Cases in Eastern Hokkaido - MAKIMURA, Shirou; INABA, Shuichi; TERAI, Tsugio; YOSHIKAWA, Takashi (JOURNAL OF THE JAPANESE ASSOCIATION OF RURAL MEDICINE, 1993)
Fifty cases of spontaneous pneumothorax treated in our hospital between 1988 and 1993 were reviewed. Forty-three cases were males and 7 cases were females. Treatments were broken down into rest cure for 11 cases and chest tube drainage for 39 cases. Of the chest tube drainage therapy cases, 30 could attained complete remission, but the remaining 9 cases required thoracotomy. In either case, the recurrence rates after the first pneumothorax and second attacks were 39% and 36%, respectively. Stature and roentgenologically determined lung sizes were also examined in 34 male patients with spontaneous pneumothorax in comparison with those of 30 healthy men, who were age-matched control subjects. Among the significant findings was that the patients were much taller than the controls. The lungs were also significantly elevated in the patients compared with those of the controls. These results indicate that the patients liable to spontaneous pneumothorax are tall with their lungs housed high in the thorax compared to the ordinary people.